Congruence in leaders-subordinates’ mindfulness and knowledge hiding: The role of emotional exhaustion and gender similarity - Wan, Jun; Liu, Zhengqiao; Zhang, Xianchun; Liu, Xiliang (Frontiers in Psychology, 2022)
Many scholars have focused on understanding ways of how to suppress knowledge hiding by employees. Existing studies have demonstrated that mindfulness could effectively inhibit employees’ knowledge hiding. This study aims to investigate the impact of leader–subordinate mindfulness congruence on subordinate knowledge hiding and its internal mechanisms. Based on the role theory, we collected 169 leadership data and 368 employee data at three time-points through collecting questionnaire of matching leaders and subordinates. In addition, we used polynomial regression and response surface analysis to validate our research hypotheses. The results demonstrated that: (i) Compared with the “high leader–high subordinate” mindfulness congruence condition, subordinates in the “low leader–low subordinate” mindfulness congruence condition were more likely to exhibit knowledge hiding. (ii) Compared with the “low leader–high subordinate” mindfulness incongruence, subordinates under the “high leader–low subordinate” mindfulness incongruence are more likely to exhibit knowledge hiding. (iii) The more incongruent the mindfulness between the leader and the subordinate is, the more likely an employee is to exhibit knowledge hiding. (iv) Emotional exhaustion mediated the correlation between leader–subordinate mindfulness congruence and knowledge hiding. (v) When the gender of the leader and the subordinate is different, the impact of mindfulness congruence on the inhibition of emotional exhaustion is stronger. This study provides a new perspective for researching the impact of mindfulness on individual behavior and provides a new idea for the research related to inhibiting knowledge hiding.